Simulation-Optimization Model for Dynamic and Sustainable Management of the Water Transfer Between two Interconnected Reservoirs: Case Study in Morocco - Laassilia, Oussama; Ouazar, Driss; Bouziane, Ahmed; Hasnaoui, Moulay Driss (Journal of Environmental Accounting and Management, 2026)
Interbasin Water Transfer (IBWT) is an efficient solution to balance the unequal temporal and spatial distribution of water resources, especially in arid and semi-arid regions. In this regard, this paper proposes a Simulation-Optimization model for reliability-based optimal sizing, operation, and water allocation of the Water Highway Project (WHP) in Morocco. Several scenarios were tested taking into account the impact of climate change on water resources both in the donor and the recipient basins. The results indicate that the increase in the transfer flow from the donor basin, as well as the increase in the storage capacity of the recipient reservoir, makes it possible to satisfy the water needs and develop the agricultural sector of the receiving region. This work has made it possible to maximize the profits of the WHP by valorizing the surplus water from the donor basin (Sebou) to meet the water needs of the receiving one (Bouregreg).